Pengaruh Program MEMBARA (Membaca Buku Bersuara) terhadap Perkembangan Literasi Anak Usia Dini (Studi Kasus Dinas Perpustakaan dan Kearsipan Kota Pekanbaru) - Azira, Sajida Diva; Rahmah, Elva (Lembaga Yasin AlSys, 2025)
The MEMBARA Program (Membaca Buku Bersuara) is an innovative digital library service that integrates digital books with audiovisual elements to enhance early childhood literacy. This study aims to examine the impact of the MEMBARA Program on early literacy development. A descriptive quantitative approach was employed, with a population of 700 MEMBARA users from January 2024 to February 2025. A total of 87 respondents were selected using purposive sampling. Data were collected via an online questionnaire distributed through Google Forms, supported by observations, and analyzed using descriptive statistics and simple linear regression with SPSS 25.0 for Windows. The results show a significant influence of the MEMBARA Program on early childhood literacy, with a correlation coefficient of 0.977 (very strong category) and a significance value of 0.000. The simple linear regression test yielded a t value of 42.414, which is greater than the critical t value of 1.666, with a significance level of 0.000 (< 0.05), indicating a statistically significant effect. The study concludes that the MEMBARA Program significantly contributes to the improvement of early childhood literacy. The findings imply that the use of audiovisual digital technology in library services can serve as an effective strategy to support literacy development from an early age.